2018
DOI: 10.1111/dme.13703
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of three prandial insulin dosing algorithms for children and adolescents with Type 1 diabetes

Abstract: The Pankowska Equation resulted in reduced postprandial hyperglycaemia at the expense of an increase in hypoglycaemia. There were no significant differences when carbohydrate counting was compared to the Food Insulin Index. Further research is required to optimize prandial insulin dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 20 publications
5
61
0
1
Order By: Relevance
“…No significant differences in postprandial glucose excursions were found when using the food insulin index compared with carbohydrate-counting. The Pankowska equation did demonstrate a reduction in glucose excursions from 90 to 240 min; however, there were significantly increased rates of hypoglycaemia, as seen in previous research [12].…”
Section: Introductionsupporting
confidence: 72%
“…No significant differences in postprandial glucose excursions were found when using the food insulin index compared with carbohydrate-counting. The Pankowska equation did demonstrate a reduction in glucose excursions from 90 to 240 min; however, there were significantly increased rates of hypoglycaemia, as seen in previous research [12].…”
Section: Introductionsupporting
confidence: 72%
“…Results from recent high-fat and/or high-protein mixed meal studies continue to support previous findings that glucose response to mixed meals high in protein and/or fat along with carbohydrate differ among individuals; therefore, a cautious approach to increasing insulin doses for high-fat and/or high-protein mixed meals is recommended to address delayed hyperglycemia that may occur 3 h or more after eating (277)(278)(279)(280)(281)(282)(283)(284)(285)(286)(287)(288)(289)(290). If using an insulin pump, a split bolus feature (part of the bolus delivered immediately, the remainder over a programmed duration of time) may provide better insulin coverage for high-fat and/or high-protein mixed meals (278,281).…”
Section: Mnt and Antihyperglycemic Medications (Including Insulin)supporting
confidence: 54%
“…However, the amount of extra insulin for a FPU has never been tested, as far as we understand. A study by Lopez et al showed that using the FPU for calculation of insulin requirements in FPRM would increase the risk for postprandial hypoglycemia [19]. Our intention was to find a solid basis for the recommendation of calculating extra insulin, as well as to provide simple and feasible instructions on how to deal with a FPRM, as the tightrope walk between optimizing control and the complexity of regulations is a well-known problem [20].…”
Section: Discussionmentioning
confidence: 99%